Intensive Monitoring Studies for Assessing Medicines: A Systematic Review - Torre, Carla; Cary, Maria; Borges, Fábio Cardoso; Ferreira, Paula S.; Alarcão, Joana; Leufkens, Hubert G.; Costa, João; Martins, Ana Paula (Frontiers in Medicine, 2019)
Introduction: Intensive monitoring (IM) is one of the methods of post-marketing active surveillance based upon event monitoring, which has received interest in the current medicines regulatory landscape. For a specific period of time, IM involves primary data collection and is actively focused on gathering longitudinal information, mainly safety, since the first day of drug use. Objectives: To describe IM systems and studies’ data published over a 11-years period (2006-2016). Specifically, we reviewed study population/event surveillance, methodological approaches, limitations and its applications in the real-world evidence generation data. Methods: We completed a systematic search of MEDLINE and EMBASE to identify studies published from 2006 to 2016, that used IM methodology. We extracted data using a standardized form and results were analysed descriptively. The methodological quality of selected studies was assessed using the modified Downs and Black checklist. Results: From 1400 screened citations, we identified 86 papers, corresponding to 69 different studies. 70% of reviewed studies corresponded to established IM systems, of which, more than half were prescription event monitoring (PEM) and modified-PEM. Among non-established IM systems, vaccines were the most common studied drugs (n=14). The median cohort size ranged from 488 (hospitals) to 10479 (PEM) patients. Patients and caregivers were the event data source in 39.1% of studies. The mean overall quality score was similar between established and non-established IM. Conclusions: Over the study period, IM studies were implemented in 26 countries with different maturity levels of post-marketing surveillance systems. We identified two major limitations: only 20% of studies were conducted at hospital-level, which is a matter of concern, insofar as healthcare systems are facing a lack of access to new medicines at ambulatory care level. Additionally, IM access to data of drug exposure cohorts, either at identification or at follow-up stages, could somehow constitute a barrier, given the complexity of managerial, linkable and privacy data issues.